Ethics of Artificial Intelligence Usage in Education: A Qualitative Study on Teachers' and Students' Perceptions - Muh Habibulloh (International Journal of Interdisciplinary Research, 2025)
The use of artificial intelligence (AI) in education is becoming increasingly widespread, offering numerous benefits while also raising ethical dilemmas. This study aims to explore teachers' and students' perceptions of AI implementation in education, highlighting its benefits, challenges, and ethical implications. Using a qualitative approach, the research involved in-depth interviews with 20 teachers and students from various high schools in Indonesia. Data were analyzed using thematic coding techniques to identify key patterns in their responses. The findings indicate that AI can enhance learning efficiency, facilitate curriculum personalization, and support educational administration management. However, concerns exist regarding algorithmic bias, personal data security, and the impact on social interactions in learning. Teachers emphasized the need for clear regulations on AI usage, while students were more focused on the benefits that technology can offer. This study concludes that although AI holds great potential in education, strict policies and ethical guidelines are necessary to ensure its balanced use and to prevent it from replacing the human role in the learning process. These findings provide valuable insights for policymakers and education practitioners in designing more ethical and effective AI implementation strategies.